2008
DOI: 10.1111/j.1365-2036.2008.03769.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum gastrin and pepsinogens do not correlate with the different grades of severity of gastro‐oesophageal reflux disease: a matched case–control study

Abstract: SUMMARY BackgroundGastrin and pepsinogens reflect the functional state of the gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
3
12
1
1
Order By: Relevance
“…In our study, we observed neither a change in the gastrin level nor in GERD occurrence between H. pylori-infected and non-infected state. In contrast to these hypotheses, we could not demonstrate any relationship between gastrin and GERD, which was comparable with a few studies in the literature (18)(19)(20)(21)(22)(23)(24). One of the reasons for this difference can be the predominant corpoantral infection in our patients.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, we observed neither a change in the gastrin level nor in GERD occurrence between H. pylori-infected and non-infected state. In contrast to these hypotheses, we could not demonstrate any relationship between gastrin and GERD, which was comparable with a few studies in the literature (18)(19)(20)(21)(22)(23)(24). One of the reasons for this difference can be the predominant corpoantral infection in our patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, it would be intriguing to predict the development of reflux esophagitis after H. pylori eradication on the basis of the serum PG I level. Nonetheless, two recent reports [48,49], one of which is our own [48], on the correlation between PG levels and the grades of gastro-esophageal reflux disease are conflicting; we have reported that serum PG I levels are elevated in long-segment Barrett's esophagus compared with controls [48], while Monkemuller et al [49] reported that serum PGs do not correlate with the different grades of severity of GERD. Further studies are required to investigate the correlation between serum PG levels and the occurrence of reflux esophagitis after eradication.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, association of NERD with H. pylori infection or atrophic gastritis is still controversial[33],[36][38]. As H. pylori infection is significantly associated with both RE and NERD in the present study (Table 2 and 4), we further analyzed the effects of H. pylori eradication on GERD patients.…”
Section: Resultsmentioning
confidence: 87%